The Knights Templar in the Kingdom of Aragon and their role in the Reconquista - oudjdi, khalfallah (The Algerian Historical Journal, 2026)
Christian sources agree that the birth of the Military Templar Corps was in the year 1118 AD, in Jerusalem, and this body, in addition to its role in protecting Christian pilgrims, played a major and dangerous role in the history of the Crusades in the Islamic East. And the role of the Knights Templar was not limited to the East only, but also reached the Iberian Peninsula, and the Kingdom of Aragon was the first Christian kingdom in which these knights appeared. And while they were there, the Islamic-Christian conflict had reached its climax, especially after the Aragon seking Alfonso I seized the city of Zaragoza, the capital of the upper border. Which made the latter think about the necessity of investing in the presence of these knights within his kingdom so that they would participate with him in his wars against the Muslims, and not long after that the Knights of the Temple became a force to be reckoned with within the Kingdom of Aragon, and they participated in its kings in all the wars they fought against the Muslims